Morphological and immunohistochemical peculiarities of placental-endometrial structures in women with benign and malignant tumors - T. D. Zadorozhna; V. V. Podolsky; O. I. Parnytska; O. I. Eschenko; S. M. Kylyhevich; T. M. Archakova; Yu. V. Davydova; N. Ya. Skrypchenko; G. O. Grebinychenko (Zaporozhye State Medical University, 2015)
Aim. Researchmaterials were the placenta of women operated on papillary carcinoma (encapsulated), endometrium of women with the same tumor markers detected in the placenta, this endometrium were taken during diagnosing postpartum catamnesis of the state of reproductive health, in comparison to the endometrium of women with benign uterine tumors (leiomyoma). Methods and results. Methods, that were used in the study: histological, immunohistochemical - indirect streptavidin-peroxidase method for detecting the expression of Ki67 Clon MIB-1, p53 Clon: DO-7, REA, Cytoceratina AE1 / AE3; Vimentin Clone: v9, receptors for estrogen (RE) and progesterone (RP). The study evaluated predictors of placental-endometrial disorders in women with cancer pathology: elevation of relative amount of expression of proliferative marker Ki-67 and p53 tumor marker in the placenta and endometrium, leading to violations in the structure of the process of regeneration; dischronosis in levels of expression of estrogen and progesterone receptors in the endometrium; presence of CEA expression in 25% of women of the main group in the endometrium and placenta; atypical glandular hyperplasia, endometrial polyps and micropolyps were found, which are important in the development of oncologic pathology.